2001
DOI: 10.1046/j.1439-0442.2001.00312.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Signs and Diagnosis of Scrapie in Italy: A Comparative Study in Sheep and Goats

Abstract: This article reports the clinical signs of scrapie occurring in sheep-goat flocks in Italy. The research, carried out on over 500 goats and 550 sheep, yielded an interesting clinical picture, especially of goat scrapie. The affected animals, aged between 2 and 8 years, showed neurological signs that could be classified into three categories: changes in mental status, abnormalities of movement and changes in sensation. Some general clinical signs were also observed. The clinical suspicion was confirmed by histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
2
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 7 publications
4
26
2
2
Order By: Relevance
“…Specifically, in the 139H scrapie model, a severe preclinical anabolic syndrome was evident and was more pronounced when hamsters were non-fasted, whereas in the HY TME model a severe catabolic syndrome developed by clinical disease and was more pronounced when hamsters were fasted. Although endocrine data associated with glucostasis are scarce from other prion disease models, sheep with clinical scrapie disease appear to also have increased concentrations of insulin and are also hyperglycemic (Viguie et al 2004) although scrapie-infected sheep actually lose weight near clinical disease onset (Capucchio et al 2001). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, in the 139H scrapie model, a severe preclinical anabolic syndrome was evident and was more pronounced when hamsters were non-fasted, whereas in the HY TME model a severe catabolic syndrome developed by clinical disease and was more pronounced when hamsters were fasted. Although endocrine data associated with glucostasis are scarce from other prion disease models, sheep with clinical scrapie disease appear to also have increased concentrations of insulin and are also hyperglycemic (Viguie et al 2004) although scrapie-infected sheep actually lose weight near clinical disease onset (Capucchio et al 2001). …”
Section: Discussionmentioning
confidence: 99%
“…In mouse models of prion disease, endocrine alterations range from hyperinsulinemia and adrenaldependent obesity to loss of body weight and reduced adiposity (Carp et al 1984, Kim et al 1987, 1988. In fact, the loss of body weight and adiposity is common in several naturally occurring prion diseases, including sheep and goats with scrapie (Capucchio et al 2001), in wild ungulates with chronic wasting disease (Miller & Williams 2002; for review see Salman 2003), and in humans with either fatal familial insomnia or CreutzfeldtJakob disease (Collinge 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Naturally-occurring scrapie in goats was first reported in France [5], and although this and other subsequent descriptions [3,16,34] record contact with scrapie-infected sheep, some others do not [15,29,34]. In most cases, the disease in goats has been reported to closely resemble that in sheep, although differences in clinical manifestation between the two species have been described [4].…”
Section: Introductionmentioning
confidence: 99%
“…Intense pruritus and obvious wool loss were not recorded as frequently as described by other authors. 4,31 All but 2 of the 129 animals in this study showed hindlimb ataxia, a nibble reflex, or both. These 2 animals were in very poor body condition (BCS, 0.5), and emaciation was the most prominent clinical finding.…”
Section: Discussionmentioning
confidence: 70%